pecial Exercises Using Assisting Apparatuses On The Development Of Some Biomechanical Variables Of Leaping In Triple Jump - Mohammed, Saif; Altay, Usama (Journal of Physical Education, 2019)
This study aimed to prepare special & aid trainings using (Vertimax and Treadmill) for the purpose of identifying some Bio Mechanical variables of triple stage in the triple jump competition, while the researcher assumed that there are no differences in the results of pre and post tests in some physical abilities and achievement and some Biomechanical variables in posttests. The experiment was applied on jumpers from the national center for talented athletes in Baghdad. The researcher used the experimental method. The subjects were tested many tests including 5 steps from static position to measure mechanical power as well as long jump from standing position to measure mechanical power of the muscle. All attempts were videotaped to find the variables 1 and 2. The researcher applied special exercises on training assisting aids for eight weeks with three training sessions per week. The researcher concluded that there is development in variable 1 after using assisting aids in training as well as increase in momentum variance which prove the lack of development in motor alignment of performance. Finally the researchers recommended using assisting aids in training according to the event as well as increasing the period of training using assisting aids for proper conditioning and adaptation. Finally the researchers recommended the necessity of periodical motor tests to identify the athlete’s weaknesses